2018
DOI: 10.3390/hydrology5030034
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Potential of OpenStreetMap Data to Improve the Accuracy of SRTM 30 DEM on Derived Basin Delineation, Slope, and Drainage Networks

Abstract: Abstract:Terrain slope and drainage networks are useful components to the basins morphometric characterization as well as to hydrologic modelling. One way to obtain the slope, drainage networks, and basins delineation is by their extraction from Digital Elevation Models (DEMs) and, therefore, their accuracy depends on the accuracy of the used DEM. Regional DEMs with high detail and accuracy are produced in many countries by National Mapping Agencies (NMA). However, the use of these products usually has associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several issues were found during the delineation of catchments on flat terrain, where computed water courses differed from the actual river network. We corrected the computed river network using the vector layers of the main rivers from Open-StreetMap (OSM), forcing the water courses following Monteiro et al (2018). The final catchments ranged from 3 to 500 km 2 with a median value of 65 km 2 and a main river length from 2.5 to 75 km with a median value of 15.2 km.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Several issues were found during the delineation of catchments on flat terrain, where computed water courses differed from the actual river network. We corrected the computed river network using the vector layers of the main rivers from Open-StreetMap (OSM), forcing the water courses following Monteiro et al (2018). The final catchments ranged from 3 to 500 km 2 with a median value of 65 km 2 and a main river length from 2.5 to 75 km with a median value of 15.2 km.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Slope angle has been confirmed as a key factor for flash-flood studies because it greatly controls the speed of the floodwaters [57][58][59][60]. This was derived from the Digital Elevation Model (DEM) with a cell size of 30 m. The DEM was extracted from Shuttle Radar Topography Mission (SRTM) database at a spatial resolution of 30 m. It should be noted that SRTM is an international project coordinated by the U.S. National Geospatial-Intelligence Agency (NGA) and the U.S. Aeronautics and Space Administration (NASA) [61]. According to Zaharia et al [62] the following slope classes have been established: 0°-3°, 3°-7°, 7°-15°, 15°-25° and > 25° (Figure 5a).…”
Section: Flash-flood Predictorsmentioning
confidence: 99%
“…OSM data is structured into four data types, namely: Nodes, ways, relations and tags [34], which are described as: The completeness and types of features available in OSM may vary considerably from region to region, as they depend upon the volunteer's contributions [35]. Usually, features such as waterways and the road network are the first to be inserted in OSM [36]. It can be seen (Figure 1c) that for study area A, most of the missing data (shown in beige) is outside the urban areas.…”
Section: Openstreetmap Datamentioning
confidence: 99%